Readiness and understanding of technical vocational education and training (TVET) lecturers in the integration of industrial revolution 4.0 - Zulnaidi, Hutkemri; Majid, Mohamad Zuber Abd (Primrose Hall Publishing Group, 2020)
This study aims to determine the readiness and understanding of Technical Vocational Education and Training (TVET) lecturers in the implementation of Industrial Revolution 4.0 (IR4.0). A total of 203 TVET lecturers in Malaysia were involved in this study, which also used descriptive and inferential statistics. Findings reveal a high level of readiness, understanding and implementation of IR 4.0 amongst the TVET lecturers. A significant relationship likewise exists amongst readiness, understanding and implementation of IR4.0. Findings also show that the TVET lecturers' understanding is a mediator of the relationship between readiness and implementation of IR4.0. Lastly, results imply that the lecturers can further enhance their effort in implementing IR4.0 to achieve the Mission of 2020. © 2020 Primrose Hall Publishing Group.